Carcass Characteristics and Meat Quality of Balitbangtan's Superior Village Chickens (KUB) Slaughtered at Different Ages - Tamzil, M. H.; Indarsih, B.; Haryanto, K. A. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The research aims to determine the effect of slaughter age on carcass characteristics and meat quality of KUB chickens kept by farmers as meat producers. The research used a completely randomized design with a unidirectional pattern using 65 un-sexed Kampung Unggul Balitbangtan (KUB) chickens. The chickens were divided into 4 slaughter age treatments, namely 4 weeks, 6 weeks, 8 weeks and 10 weeks. At each slaughter age, 15 chickens are used as replications. All chickens in the slaughter age group are slaughtered using the bleeding method in the neck area by cutting off the respiratory tract, blood vessels and digestive tract. After the chicken is declared dead, it is dipped in warm water (temperature 80oC), then the feathers are cleaned, the head and neck, legs are cut and the internal contents are removed. For the purposes of measuring meat quality, meat samples were taken from the chest and then measured at the Animal Products Processing Technology Laboratory, Faculty of Animal Husbandry, Mataram University. Slaughter age increased live weight, lower thigh weight percentage, meat cooking loss value (P<0.01), carcass weight percentage, wing weight percentage, upper thigh weight percentage, and water holding capacity (P<0.05), but did not affect breast weight percentage , back weight and meat pH (P>0.05). It was concluded that delaying the age of slaughter increases the edible part and decreases the inedible part. This research delays the age of slaughter to increase the edible part and reduce the inedible part.